Pengaruh Media Sambung Huruf Terhadap Peningkatan Hafalan Mufrodat Bahasa Arab Bahasa Arab Peserta Kursusan Al-’Alam Asrama Darul Lughoh Al-‘Arabiyyah Pondok Pesantren Darussalam Putri Utara Blokagung Banyuwangi Tahun Pelajaran 2020/2021 - Ro’fat Hizmatul Himmah; Winda Khoritotul Jannah (TADRIS AL-ARABIYAT: Jurnal Kajian Ilmu Pendidikan Bahasa Arab, 2022)
This research is motivated by a lack of confidence in themselves, lack of motivation in learning Arabic, often course participants hear mufrodat bahasa arab or sentences without knowing the correct writing, even though in Arabic there is a difference between pronunciation and writing, besides course participants al- Darul Lughoh al-'arabiyyah dormitory nature still uses the usual or manual memorization method without using the media. This research was conducted at the Darul Lughoh Al-'Arabiyyah Islamic Boarding School Darussalam Putri Utara, Blokagung Banyuwangi with the research object of the al-'alam course participants who were in the dormitory. A dapun objectives in this study are 1. To find out the application of letter-dial media in learning Arabic in the Al-Alam Darul Luhgoh Al-'Arabiyyah Dormitory course. 2. To find out the improvement of mufrodat bahasa arab memorization in the Al-'Alam Asrama Darul Luhoh Al-'Arabiyyah course. 3. To find out the effect of letter-dial media on improving mufrodat bahasa arab memorization in the Al-'Alam Darul Lughoh Al-'Arabiyyah Dormitory course This research is a quantitative research. Which is used to find out how effective is the effect of letter-dial media on increasing mufrodat bahasa arab in al-'alam course participants. Data were taken using Question, questionnaires, and. Meanwhile, to test whether the items are valid or not, the product moment formula is used . In this study, after testing the hypothesis, the following results can be obtained: 1) Improved memorization of mufrodat bahasa arab participants of the Darul Lughoh al-'arabiyyah boarding Arabic course with a positive correlation of 65.968 . The correlation with a value of 65.985 or 66 lies in the interval between 63 - 68 which is included in the fairly good category. 2) The effect of letter-dial media on increasing mufrodat bahasa arab (X) memorization on increasing mufrodat bahasa arab (Y) memorization. Based on the results of the f test, the result is that fcount is 53,259 compared to f table with N = 31 significance level 5% = 4.18 resulting in f test results > from f table, then Ha is accepted. 3) The research shows the results of 64 % the remaining 37 % . This means that when viewed from the index of significance value, the influence of letter-dial media has an effect on increasing memorization in the Al'- Alam Darul Lughoh Al-'Arabiyyah Dormitory course